A novel one‐step reaction sodium‐sulfur battery with high areal sulfur loading on hierarchical porous carbon fiber. Issue 3 (19th October 2020) - Guo, Qiubo; Sun, Shuo; Kim, Keun‐il; Zhang, Hongshen; Liu, Xuejun; Yan, Chenglin; Xia, Hui
Abstract: Room temperature sodium‐sulfur (RT Na‐S) batteries are gaining extensive attention as attractive alternatives for large‐scale energy storage, due to low cost and high abundancy of sodium and sulfur in nature. However, the dilemmas regarding soluble polysulfides (Na2 S n, 4 ≤  n  ≤ 8) and the inferior reaction kinetics limit their practical application. To address these issues, we report the activated porous carbon fibers (APCF) with small sulfur molecules (S2 – 4 ) confined in ultramicropores, to achieve a reversible single‐step reaction in RT Na‐S batteries. The mechanism is investigated by the in situ UV/vis spectroscopy, which demonstrates Na2 S is the only product during the whole discharge process. Moreover, the hierarchical carbon structure can enhance areal sulfur loading without sacrificing the capacity due to thorough contact between electrolyte and sulfur electrode. As a consequence, the APCF electrode with 38 wt% sulfur (APCF‐38S) delivers a high initial reversible specific capacity of 1412 mAh g −1 and 10.6 mAh cm −2 (avg. areal sulfur loading: 7.5 mg cm −2 ) at 0.1 C (1 C = 1675 mA g −1 ), revealing high degree of sulfur utilization. This study provides a new strategy for the development of high areal capacity RT Na‐S batteries. Abstract : The activated hierarchical porous carbon fibers host with 38 wt% metastable sulfur molecules (APCF‐38S) anchored in the slit‐like ultramicropores are used as working electrode in RT Na‐S batteries. During the discharge process, there is only one product‐Na2 S can be detected. The electrode delivers a high areal capacity of 10.6 mAh cm −2 with areal sulfur loading of 7.5 mg cm −2 .